- Judaism in the interpretation of Rashid ALKhatib ALMusli - Comparative analytical study - Ismail, Frist Marai (Journal of Islamic Sciences, 2018)
This research concerns the position of the interpreter Rashid AL Khatib Al-Musli of Jews and Judaism. It seems that the interpreter relied very much on the interpretation of Al-Manar by Sheikh Mohammed Rashid Rida in explaining the different aspects of this religion. Because, according to his belief, the matter has been fulfilled. But what is taken on our interpreter not to address the subject of the Israeli occupation of Palestine and the establishment of the Jewish state on 15/5/1948. He had first written non-continuous verses, and then wrote a complete continuation, and then reviewed for the fourth time interested in revision and refinement, and introduced a lot of reform. It was then launched for the fifth time on 29/5/1944 and completed on 21/3/1946. It was printed in 1974 at the University of Mosul Press. The author could add to the Jews and the establishment of the so-called Hebrew state to its interpretation after its founding on 15/5/1948.
Keywords: The Jews; Judaism; Israel; Interpretation; Rashid Al Khatib Al Musli